(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
TDR, The Drama Review, is the first and most important Performance Studies journal. It has existed for more than half a decade, it testifies to the birth of this field of research and its following main developments. By going through the history of the journal, this short overview shows how TDR is engaged in a genuine mutual osmosis between what appears on its pages and what is happening in the world of performance practice, studies, and research.